Comparison of PJOK Teachers' Teaching Skills in terms of Students' Logical Thinking Skills - Satya Hasmara, Puguh; Nurhasan, Nurhasan; Suroto, Suroto; Ma’arif, Ilmul (International Journal of Educational Research & Social Sciences, 2023)
In the future, we will face several challenges and changes that demand a change in the educational paradigm that has been applied by teachers in Indonesia. Students from now on should be accustomed to searching for information on their own, be able to identify and formulate problems, be able to work effectively in group work and have high logic. In Indonesia, there are two residential layouts called urban and rural. At this time everyone in the city and in the village, be it teachers or students already have qualified sources of information, both from the internet, television, or from other social media.The purpose of this study is to determine the comparison of PJOK teachers' teaching skills in terms of students' creative thinking skills in public junior high school students in urban and rural Jombang Regency. This study is a comparative study. Researchers use a type of comparative research (comparative research. Researchers used a sample of class VII I A SMPN 1 Ploso (village school) with a total of 32 students and class VIII A SMPN 1 Diwek (city school) with a total of 32 students.Based on the calculation of all data obtained by researchers from SMPN 1 Ploso (village school) and SMPN 1 Diwek (city school) obtained t count of 2.212 which was then compared with t table at the level of significance of 5% with the number of respondents 32 students with df = n – 1 obtained t table with an interpretation of 1.999 Thus it can be known t table < t count. Based on the results of the discussion described above, it can be concluded that, there are significant differences in the teaching skills of PJOK teachers at SMP N 1 Ploso (village school) and SMP N 1 Diwek (city school). The teaching skills of PJOK teachers at SMP N 1 Diwek are better than the teaching skills of PJOK teachers at SMP N 1 Ploso, when viewed from the creative thinking of students in each of these junior high schools.